Improving the performances of low concentration electrolytes via dual interfacial modification of the fluoroethylene carbonate solvent and lithium difluoro(oxalato)borate additive. (20th September 2022) - Quan, Yin; Gao, Cankun; Wu, Shumin; Zhao, Dongni; Wang, Jie; Li, Chunlei; Li, Shiyou
Abstract : A cathode electrolyte interphase with abundant C–F in the outer layer and abundant LiF in the inner layer is formed. Abstract : The high price of lithium salts hinders the sustainable development of high concentration electrolytes, while the poor electrochemical performance limits the large-scale application of low concentration electrolytes. Herein, the electrochemical performance of a low concentration electrolyte is improved via dual interfacial modification of the fluoroethylene carbonate (FEC) solvent and the lithium difluoro(oxalato)borate (LiODFB) additive. LiODFB is preferentially oxidized via a ring-opening path to generate a lithium fluoride (LiF)-rich inner layer on the surface of a ferrous lithium phosphate cathode, and then a large amount of C–F polycarbonate oligomers is generated in the outer layer via a reaction between LiODFB and FEC. LiF has a large bandgap and a low lithium ion (Li + ) diffusion barrier, and the electronegative C–F groups provide the lithiophilic sites to reduce the interaction between Li + and solvents, resulting in a repulsive force towards the CO dipole of the carbonate ester solvent to improve the oxidation stability of the electrolyte. The clever design of the multi-layer cathode electrolyte interphase suppresses the excessive decomposition of the electrolyte, improves the diffusion of Li +, and enables much-improved cycling stability of the cathodes. This work gives a fruitful insight into the key role of cathode electrolyte interphase components in Li + diffusion and improves the performance of low-concentration electrolytes.